The Influence of the Picture and Picture Model with the JAS Approach on Cognitive Learning Outcomes and Student Creativity at SMA Negeri 1 Jakenan - Suharni; Sukaesih, Sri (Universitas Negeri Semarang, 2024)
The The demands of 21st century learning and the Independent Curriculum have not been fully implemented well, especially the creative abilities of students at SMA N 1 Jakenan. Based on observations made at SMA Negeri 1 Jakenan, it was found that students were less active during learning so that students' creativity was less developed. Students also still need additional learning resources apart from using LKPD and textbooks. This research aims to analyze the influence of the Picture and Picture model with the JAS approach (PICJAS) on students' cognitive and creative learning outcomes in Plantae material. This research is a type of quasi-experimental research with a Pretest-Posttest Nonequavalent Control Group Design. The samples used in this research were X3 (experimental class) and X4 (control class) which were taken using purposive sampling technique. The data collection technique in this research is using tests, product assessment, observation and giving questionnaires. Data analysis was carried out using the independent sample t-test for student cognitive learning outcomes and the Mann Whitney test for student creativity outcomes. Based on data analysis using the independent sample t-test and the Mann Whitney test, a significance value of 0.00 and 0.00 was obtained, because the sig value < α (0.05) means that there is a significant difference between the classes given the model treatment. PICJAS with classes treated with the lecture and discussion method or H0 is rejected and H1 is accepted. These results show that there is a significant influence from implementing the PICJAS learning model on improving students' cognitive learning outcomes and creativity. This influence can make the PICJAS model an alternative learning model that can improve students' cognitive learning outcomes and creativity.